El modelo transteórico como experiencia comunitaria en la separación de residuos sólidos domiciliarios para la recuperación de materiales y reducción de la cantidad de desechos (2011)
The processes of change are cognitive, affective and experiential strategies used for people to change their behavior. In the perspective of health-promoting interventions, these processes are the facilitating and accelerating core, which represent basic and responsible principles for expected behavioral changes.  In the Transtheoretical Model, these processes are the key to be applied in the design of the strategy “Separate what you throw before throwing it to the trash”, promoting intervention of environmental health with direct or indirect behavioral impacts that catalyze transitions from one stage to another in the sequence.